Answer:
Explanation:
We are given that
![f(x)=6((1)/(3))^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/n231ecnuoeg0v7g3bacu8jtjal6inc5mlk.png)
Function f decreases from quadrant 2 to quadrant 1 and approaches y=0
It cut the y- axis at (0,6) and passing through the point (1,2).
Function g(x) approaches y=0 in quadrant 2 and increases into quadrant 1.
It passing through the point (-1,2) and cut the y-axis at point (0,6).
Reflection across y- axis:
Rule of transformation is given by
![(x,y)\rightarrow (-x,y)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ll07l9k1nyw3jiyp0uv6bo573wuv85z2c5.png)
Using the rule then we get
![g(x)=6((1)/(3))^(-x)=6(3)^x](https://img.qammunity.org/2021/formulas/mathematics/high-school/aqz4vrcjnmpaq34g582tyxh9mx5lpwtw38.png)
By using
![x^(-a)=(1)/(x^a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ld3rb9zmhkdtlv85iydnfj6corshknkdwd.png)
Substitute x=-1
![g(-1)=6* ((1)/(3))=2](https://img.qammunity.org/2021/formulas/mathematics/high-school/imzjqme1b9s4wegp86eld6qhyazqvkkw99.png)
Substitute x=0
![g(0)=6](https://img.qammunity.org/2021/formulas/mathematics/high-school/eem78c8do845yxm3gka1rbvr3auyzlv0ov.png)
Therefore,
is true.